Investigating Theory of Planned Behavior on Customers' Decision to Choose Islamic Banks: Evidence from Surakarta, Indonesia - Nisa, Siska Khoirun; Haris, Helmi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
This study aimed to see the influence of Attitude, Subjective Norms, and Perceived Behaviours Control with religiosity as a moderating variable on the decision to become a customer of a Sharia bank in Surakarta. Currently, the use of sharia banks is increasing every year, including the city of Surakarta, which is predominantly Muslim. For this reason, it is necessary to conduct research related to the decision. What distinguishes it from similar studies is adding the religiosity variable as a moderating variable. This study uses the Theory of Planned Behavior. This study distributed questionnaires to 100 respondents who met the requirements to obtain survey results-hypothesis testing using SEM with Smart-PLS software version 3.0. The results of the hypothesis test show that the three variables of the Theory of Planned Behaviour significantly positively affect the decision to become a customer of a Sharia bank. The influence of Subjective Norms shows that religiosity can strengthen the impact of Subjective Norms on the decision of the community to become a customer of a Sharia bank. Meanwhile, Attitude and Perceived Behaviour Control after being moderated by religiosity show results that religiosity can weaken the influence of Attitude and Perceived Behaviour Control on the decision to become a customer of a Sharia bank.